AMPA Receptors Are Involved in Store-Operated Calcium Entry and Interact with STIM Proteins in Rat Primary Cortical Neurons - Gruszczynska-Biegala, Joanna; Sladowska, Maria; Kuznicki, Jacek (Frontiers in Cellular Neuroscience, 2016)
The process of store-operated calcium entry (SOCE) leads to refilling the endoplasmic reticulum (ER) with calcium ions (Ca2+) after their release into the cytoplasm. Interactions between (ER)-located Ca2+ sensors (stromal interaction molecule 1 [STIM1] and STIM2) and plasma membrane-located Ca2+ channel-forming protein (Orai1) underlie SOCE and is well described in non-excitable cells. In neurons, however, SOCE appears to be more complex because of the importance of Ca2+ influx via voltage-gated or ionotropic receptor-operated Ca2+ channels. We found that the SOCE inhibitor ML-9 and SKF96365 reduced AMPA-induced [Ca2+]i amplitude by 80% and 53%, respectively. To assess the possible involvement of AMPA receptors in SOCE, we used their specific inhibitors. As estimated by Fura-2 AM single-cell Ca2+ measurements in the presence of CNQX or NBQX, thapsigargin-induced Ca2+ influx decreased 2.2 or 3.7 times, respectively. These results suggest that under experimental conditions of SOCE when Ca2+ stores are depleted, Ca2+ can enter neurons also through AMPA receptors. Using specific antibodies against STIM proteins or GluA1/GluA2 AMPA receptor subunits, co-immunoprecipitation assays indicated that when Ca2+ levels are low in the neuronal ER, a physical association occurs between endogenous STIM proteins and endogenous AMPAR receptors. Altogether, our data suggest that STIM proteins in neurons can control AMPA-induced Ca2+ entry as a part of the mechanism of SOCE.